Axes: a new paradigm of regional planning? Infrastructure axes in the national PPAs, in the Iirsa and in the macrometrópole paulista - Tavares, Jeferson Cristiano (Pontifícia Universidade Católica de São Paulo, 2016)
Our goal is to discuss inter-scalar territorial organization based on the infrastructure axes proposed by the government between 1995 and 2015. Our analysis is grounded on the theoretical framework that shows the relationship between (re)structuring of production and territorial organization (Logan; Molotch, 1987; Scott, 1980; Brenner, 2010). We chose to study planning actions proposed by public initiative. At the federal level: the PPAs and their programs; at the continental level: the plans and proposals of the Iirsa; and at the state level: the Plano de Ação da Macrometrópole Paulista (PAM 2013-2040). Our findings point to the ongoing leading role of the Axis as a structuring element of territorial organization in its different scales, guided by the principles of integration, connectivity and competitiveness.